Classical solutions of parabolic initial-boundary value problems and Hormander spaces. - Los’, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
For the second-order linear parabolic differential equations with complex-valued coefficients, we establish new sufficientconditions under which the generalized solutions of these problems are continuous. The conditions are formulated in theterms of belonging of the right-hand sides of these problems to certain anisotropic Ho¨rmander spaces.